2021
DOI: 10.1155/2021/4717349
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Is Correlated with Blood Pressure in Obstructive Sleep Apnea Patients

Abstract: Background. Despite approximately 95% primary cases of hypertension, secondary hypertension seems to be common with resistant forms. Notably, obstructive sleep apnea (OSA) is known as a common cause of secondary hypertension and has a major characteristic of obesity. Irisin acts as a link between muscles and adipose tissues in obesity, playing an essential role in human blood pressure (BP) regulation. However, whether irisin is associated with secondary hypertension caused by OSA and how it takes effect essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…So, in women and men, the only blood pressure measurement related with irisin was DBP. Even though previous studies have described systolic and diastolic blood pressure correlations with irisin, they did not adjust physical activity and this is crucial for this exerkine; in addition their sample sizes were small and the authors recognize the need of future studies with larger sample sizes (21,22). It has been suggested that irisin plays a role in blood pressure control, perhaps acting as cofactor to modulate vascular function, so a balanced serum level of irisin would be essential in maintaining vascular tone (23).…”
Section: Discussionmentioning
confidence: 99%
“…So, in women and men, the only blood pressure measurement related with irisin was DBP. Even though previous studies have described systolic and diastolic blood pressure correlations with irisin, they did not adjust physical activity and this is crucial for this exerkine; in addition their sample sizes were small and the authors recognize the need of future studies with larger sample sizes (21,22). It has been suggested that irisin plays a role in blood pressure control, perhaps acting as cofactor to modulate vascular function, so a balanced serum level of irisin would be essential in maintaining vascular tone (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have been conducted to investigate the association between irisin levels and blood pressure in humans. Positive correlations have been found between irisin levels and blood pressure in obstructive sleep apnoea patients [38]. Similarly, a study including 24 obese and 63 normal-weight children has found that irisin levels are positively correlated with systolic and diastolic blood pressure [39].…”
Section: Introductionmentioning
confidence: 94%